A Heart Rate Based Algorithm to Estimate Core Temperature Responses in Elite Athletes Exercising in the Heat - de Korte, Johannus Q.; Veenstra, Bertil J.; van Rijswick, Mark; Derksen, Eline J. K.; Hopman, Maria T. E.; Bongers, Coen C. W. G.; Eijsvogels, Thijs M. H. (Frontiers in Sports and Active Living, 2022)
Purpose Non-invasive non-obtrusive continuous and real-time monitoring of core temperature (Tc) may enhance pacing strategies, the efficacy of heat mitigation measures, and early identification of athletes at risk for heat-related disorders. The Estimated Core Temperature (ECTemp™) algorithm uses sequential heart rate (HR) values to predict Tc. We examined the validity of ECTemp™ among elite athletes exercising in the heat. Methods 101 elite athletes performed an exercise test in simulated hot and humid environmental conditions (ambient temperature: 31.6 ± 1.0°C, relative humidity: 74 ± 5%). Tc was continuously measured using a validated ingestible telemetric temperature capsule system. In addition, HR was continuously measured and used to compute the estimated core temperature (Tc−est) using the ECTemp™ algorithm. Results Athletes exercised for 44 ± 10 min and n = 5,025 readouts of Tc (range: 35.8–40.4°C), HR (range: 45–207 bpm), and Tc−est (range: 36.7–39.9°C) were collected. Tc−est demonstrated a small yet significant bias of 0.15 ± 0.29°C (p < 0.001) compared to Tc, with a limit of agreement of ±0.45°C and a root mean square error of 0.35 ± 0.18°C. Utilizing the ECTemp™ algorithm as a diagnostic test resulted in a fair to excellent sensitivity (73–96%) and specificity (72–93%) for Tc−est thresholds between 37.75 and 38.75°C, but a low to very-low sensitivity (50–0%) for Tc−est thresholds >39.0°C, due to a high prevalence of false-negative observations. Conclusion ECTemp™ provides a valuable and representative indication of thermal strain in the low- to mid-range of Tc values observed during exercise in the heat. It may, therefore, be a useful non-invasive and non-obtrusive tool to inform athletes and coaches about the estimated core temperature during controlled hyperthermia heat acclimation protocols. However, the ECTemp™ algorithm, in its current form, should not solely be used to identify athletes at risk for heat-related disorders due to low sensitivity and high false-negative rate in the upper end of the Tc spectrum.